2014
DOI: 10.3389/fphar.2014.00124
|View full text |Cite
|
Sign up to set email alerts
|

The physiological functions of iron regulatory proteins in iron homeostasis - an update

Abstract: Iron regulatory proteins (IRPs) regulate the expression of genes involved in iron metabolism by binding to RNA stem-loop structures known as iron responsive elements (IREs) in target mRNAs. IRP binding inhibits the translation of mRNAs that contain an IRE in the 5′untranslated region of the transcripts, and increases the stability of mRNAs that contain IREs in the 3′untranslated region of transcripts. By these mechanisms, IRPs increase cellular iron absorption and decrease storage and export of iron to maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
182
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(195 citation statements)
references
References 99 publications
(164 reference statements)
2
182
0
11
Order By: Relevance
“…Glrx3⅐[2Fe-2S]⅐BolA2 complexes may be analogous to the labile iron pool and serve to make [2Fe-2S] clusters available to apoproteins or the cytosolic [4Fe-4S] distribution machinery, essentially functioning as [2Fe-2S] cluster chaperones. The wide dynamic range and kinetic lability of the Glrx3⅐[2Fe-2S]⅐BolA2 complexes are reminiscent of the iron-sensing, iron-regulatory protein 1 (IRP1), which responds to increases in cellular iron availability by rapidly coordinating a [4Fe-4S] cluster (49,50). Cluster coordination allows IRP1 to shift from an RNA-binding protein to an enzyme; thus, IRP1 acts as an iron sensor and post-transcriptional regulator of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Glrx3⅐[2Fe-2S]⅐BolA2 complexes may be analogous to the labile iron pool and serve to make [2Fe-2S] clusters available to apoproteins or the cytosolic [4Fe-4S] distribution machinery, essentially functioning as [2Fe-2S] cluster chaperones. The wide dynamic range and kinetic lability of the Glrx3⅐[2Fe-2S]⅐BolA2 complexes are reminiscent of the iron-sensing, iron-regulatory protein 1 (IRP1), which responds to increases in cellular iron availability by rapidly coordinating a [4Fe-4S] cluster (49,50). Cluster coordination allows IRP1 to shift from an RNA-binding protein to an enzyme; thus, IRP1 acts as an iron sensor and post-transcriptional regulator of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…transferrin receptor) of translation (reviewed in [209,210]. While early studies of mammalian cells lacking IRP1 or IRP2 indicated that IRP2 is the principal sensor of iron, recent studies have revealed that IRP1 plays essential functions in erythropoiesis and in pulmonary and cardiovascular systems [211].…”
Section: Iron Regulatory Protein 1 (Irp1)mentioning
confidence: 99%
“…The testicular immune privilege is a complex mechanism developed in the testicular compartment to maintain the balance local of pro/anti-inflammatory cytokine levels [31], involved in regulation the synthesis of SF [32] and intracellular iron ion level via the ion regulatory protein (IRP) [33]. Mechanisms of functional interactions between germ cells and Sertoli cells; Sertoli cells and Leydig cells, known as autocrine/ paracrine regulation and hematopoietic barrier, are also part of the mechanism of testicular immune privilege protecting germ cells from effect inflammatory/oxidative/ionic toxicity [34].…”
Section: Fertility Index (Fi) and Seminal Parameters (Sp)mentioning
confidence: 99%